Improving impact toughness of Fe–20Mn–9Al-1.5C–2Ni–3Cr low-density steel by optimizing grain boundaries via multi-stage heat treatment without compromising high strength and ductility - Lei Xiao; Yanjun Zhou; Chuheng Zhang; Yangyang Wang; Xiangtao Deng; Zhaodong Wang (Journal of Materials Research and Technology, 2024)
Fe–20Mn–9Al-1.5C–2Ni–3Cr low-density steel is subjected to multi-stage heat treatment (MHT) to improve the toughness while maintaining high strength and ductility. The mechanical properties and fracture behavior of MHT steel are compared with those resulting from single-stage heat treatment (S1000 and S1050) usnig SEM, EBSD, and TEM microstructural characterization. The grain sizes of S1000, S1050 and MHT are 3.17, 3.84, and 7.31 μm, respectively. The proportion of “special” grain boundaries changes from 71.7 % to 68.3 % and finally to 71.2 % (by length). Simultaneously, dissolution of intergranular Cr7C3 precipitates in S1000. The half-size impact energy of MHT is 88.6 % higher than that of S1000, reaching 55.1 J, and the ultimate tensile strength and total elongation are maintained at approximately 1100 MPa and 50 %, respectively. As demonstrated by quantitative analysis, the yield strength is maintained at 910 MPa due to solution, grain boundary, and precipitation strengthening, whereas the increase in toughness is due to the rise in the crack propagation energy. The increased toughness is derived from the combined effect of reducing the number of intergranular precipitates and a high percentage of “special grain boundaries''.